Experimental research on the flow law of the grouting fluid in an annular gap between a non-soil-squeezing PHC pipe pile wall and a hole wall - Zhenkun, Hou; Zhanlin, Li; Zejun, Han; Mengxiong, Tang; Yupeng, Liu; Dingli, Su; Lei, Wang (Frontiers in Ecology and Evolution, 2023)
The bearing capacity of drilling with pre-stressed concrete pile cased pile (hereafter referred to as DPC pile) is closely related to the grouting effect on an annular gap between a pre-stressed high-strength concrete (PHC) pipe pile wall and a hole wall (hereafter referred to as the an annular pile–soil gap). A physical grouting model testing system for the DPC pile based on a high-precision three-dimensional (3D) scanner and a multi-functional grouting box has been independently developed. In this method, 3D geometric size and spatial point information of the grouting stone have been quantitatively characterized. The influences of the water–cement ratio, grouting pressure, collapsed holes, and falling sand have been studied. The conclusions are obtained as follows: (1) a quantitative characterization method of the 3D geometric dimensions of the grouting stone based on a 3D scan is accurate and reliable and can overcome the shortcomings of traditional manual measurement. (2) In the same horizontal plane, grouting body thickness gradually decreases as its horizontal distance from the grouting outlet increases, and the higher the elevation, the greater the rate of decrease; conversely, the lower the elevation, the slower the rate of decrease. When the horizontal distance from the pulp outlet is equal, slurry thickness gradually decreases as the height increases. (3) For the grouting liquid with a water–cement ratio of 0.5, grouting pressure should not be less than 0.6 MPa. (4) When the falling sand is not far above the grouting outlet, a grouting root system can be formed, whose grout veins, complexity, and grout coverage area can be optimally improved by changing the fluidity of the grout and grouting pressure. When the falling sand is on the side of the grouting outlet or the surface of the grouting outlet but far away from the grouting outlet, it is easy to be avoided by the grout, which can greatly reduce the grouting effect.